Bids and asks in disequilibrium market microstructure: The case of IBM - deB. Harris, Frederick H.; McInish, Thomas H.; Chakravarty, Ranjan R. (Journal of Banking & Finance, 1995)
Microstructure research has recently forged two theoretical frameworks characterizing stock specialist behavior: a Walrasian inventory-theoretic individual optimization model sometimes with asymmetric information, and a queue-theoretic disequilibrium market model of the continuous auction process. To test the Brock and Kleidon (Journal of Economic Dynamics and Control, 16 (1992) 451–489) continuous auction process, two simultaneous autoregressive equations for ask prices and for bid prices are estimated using transactions data for IBM for calendar year 1988. The results support Brock and Kleidon's distinguishing implications — namely, increased trading volume raises the ask and lowers the bid, and a Hausman-type specification test fails to reject the exogeneity of order flows at the bid and the ask. Also, greater price volatility within a fifteen minute interval leads to both lower bids and lower asks as buyers are accorded a risk premium, consistent with Brown, Harlow and Tinic's (Journal of Financial Economics, 22 (1988) 355–385) uncertain information hypothesis for efficient markets.